Metabarcoding revela variação na composição da comunidade bentônica do substrato inconsolidado no Arquipélago dos Alcatrazes - Ferreira, Amanda do Pinho Cândido (Universidade Federal de São Carlos, 2026)
Subtidal marine ecosystems harbor rich biological diversity and play a fundamental role in maintaining global biogeochemical cycles and ocean health. However, monitoring these communities, particularly in unconsolidated substrates, faces the challenges of morphological taxonomic identification. This study used environmental DNA (eDNA) metabarcoding of the Cytochrome oxidase I (COI) gene to investigate the fauna of the subtidal unconsolidated substrate at three sites in the Alcatrazes Archipelago (ESEC, Wolverine, and Geladeira) along a distance gradient from the rocky shore, seeking to understand their spatial structuring. Sediment samples were collected in triplicate, total DNA was extracted, and the COI gene was amplified and sequenced on the Illumina platform. Taxonomic assignment was performed by comparison with the MIDORI2 database. The results revealed significant biological heterogeneity among the sampled sites, with ESEC showing greater absolute richness and Wolverine standing out for its taxonomic uniqueness, with 18% to 20% of exclusive taxa. In contrast, the Geladeira site demonstrated a more simplified community structure, suggesting the influence of local environmental filters on species selection. The analysis of indicator taxa demonstrated the presence of ubiquitous genera (such as Margalefidinium) and others found in only one of the sites, such as Pseudoparamoeba at Wolverine. The disparity between observed richness and the Chao1 estimator indicated that the actual biodiversity in these locations remains underestimated. No significant influence of the distance gradient from the rocky shore was observed on community richness and composition, suggesting a homogeneous distribution of the sediment-associated fauna at the analyzed scale. This study expands knowledge about local biodiversity and provides support for the monitoring of this conservation unit.
Metabarcoding reveals variation in the composition of the benthic community on unconsolidated substrate in the Alcatrazes Archipelago
Keywords: eDNA; Comunidade bentônica; metabarcoding; Biodiversidade marinha; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS; 14. Vida na Água